Penggunaan Laboratorium Alam dalam Peningkatan Kemampuan Menulis Deskripsi Bahasa Indonesia Pada Siswa Kelas X TKJ 2 SMKN 3 Soppeng - Desy Ayu Andhira (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study aims to describe: (1) planning the use of natural laboratories in improving description writing skills, (2) implementation of the use of natural laboratories in improving description writing skills, (3) assessment of the use of natural laboratories in improving description writing skills in class X TKJ 2 students of SMKN 3 Learning Year 2024-2025. This research is a class action research, which includes preliminary study, planning, action implementation, observation, and reflection. This research data is in the form of learning process data and action product data obtained from observations and documentation of student essay results. The main instruments in this research are partner teachers and researchers who act as data collectors by using supporting instruments in the form of observation formats, field notes, and documentation review of student essay results. The research data analysis was carried out based on the stages, namely data reduction, data presentation, and conclusion drawing. The results of the preliminary study of writing learning in students of class X TKJ 2 SMKN 3 Soppeng show that students' essays are still relatively poor. This is evidenced by the results of the pre-action data that out of 23 students, there were no students with excellent qualifications, 7 students with good qualifications or 30.43%, 9 students with sufficient qualifications or 39.13%, 4 students with poor qualifications or 17.39%, and 3 students failed 13.05%. Thus, it can be said that the results of the pre-action test corroborate the findings of the preliminary study of students in class X TKJ 2 SMKN 3 Soppeng having difficulty in writing descriptions. After taking action through cycle I and cycle II, the results of students' essays showed a significant increase.